EDUCATION FOR SUSTAINABLE DEVELOPMENT AS AN AXIOLOGICAL, NORMATIVE, AND PHILOSOPHICAL-EDUCATIONAL MODEL WITHIN THE FRAMEWORK OF THE SUSTAINABLE DEVELOPMENT GOALS - Polishchuk, Viktor (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The article examines the problem that the normative consolidation of Education for Sustainable Development (ESD) is insufficient for its effective implementation. Without philosophical clarification of the concepts of development, rationality, nature, and education, ESD risks remaining declarative while economic growth continues to dominate social and ecological dimensions. The aim and tasks. The aim of the study is to substantiate that ESD functions within the structure of the Sustainable Development Goals (SDGs) as an axiological, normative, and philosophical-educational model necessary for integrating the social, ecological, and economic dimensions of sustainability. The tasks include analysing critiques of anthropocentrism, instrumental reason, and economic reductionism; clarifying the concept of development in ESD; examining conditions for integrating the three sustainability dimensions; and substantiating the pedagogical implementation of ESD through value-competency and whole-institution approaches. Research methods. The study applies philosophical-educational analysis combining comparative-analytical, hermeneutic, systemic, and critical-conceptual approaches. Research results. The philosophical foundations of ESD are revealed through the critique of anthropocentrism, instrumental reason, and economic reductionism. Development is interpreted not as one-dimensional economic growth but as an axiologically oriented process. The analysis demonstrates that formally integrative educational models may preserve economic reductionism without reconsidering dominant rationality. The study also shows that competency-based ESD approaches require deliberate pedagogical formation of value-oriented and reflective dimensions. Discussion. A tension is identified between UNESCO normative approaches focused on measurable competencies and philosophical-educational approaches oriented toward the transformation of rationality and values. These approaches are complementary rather than identical. Conclusions. ESD is substantiated as a constitutive element of the SDGs structure rather than an auxiliary educational instrument. It functions as a mechanism of axiological and reflective transformation through which sustainable development becomes a practical educational and social process.